Sexually Transmitted Infections in Men having Sex with Men - Rising Numbers and Wider Etiologies - Soriano, Vicente (AIDS Reviews, 2019)
Classical sexually transmitted infections (STI), namely, syphilis, gonorrhea, trichomonas, and chlamydia, are on the rise worldwide.
Keywords: JCR; Scopus